Implementing TPOA: Telecentre Programme for Orang Asli (Poster) - Universiti Malaysia Sarawak, Institute Of Social Informatics and Technological Innovations (Universiti Malaysia Sarawak (UNIMAS), 2015)
Poster exhibited at Karnival Pengajian Tinggi